Hydrophobically Modified Pegylated Chitosan Derivative: Synthesis, Characterisation And Formulation Of Nanoparticles - Chong, Wai Mun (2021)
Hydrophobic drugs encounter limitations such as poor solubility, vulnerable to degradation in biological environment and lack of selectivity towards targeted cells thus reduced the drug delivery and therapeutic efficacy. Drug-loaded nanoparticles (NPs) are widely studied for their potential to improve the conventional medication by increasing the drug solubility and targeting of the diseased sites. Glycol chitosan (GC) is a versatile material as a nanocarrier as its structure can be modified, soluble in wide range of pHs, biocompatible and non-toxic. Itraconazole (ITZ) can be repurposed into an anticancer drug as it is capable of inhibiting growth of several types of cancer cells. The aim of this study was to develop palmitoylated GC polymer grafted with poly(ethylene) glycol (PEG) (PGC-PEG) and formulate the polymer with ITZ into stable NPs formulations. PGC-PEG was synthesised in a stepwise manner involving acid degradation, PEGylation and palmitoylation. The characterisation of several batches of PGC-PEG revealed polymer with 3.3% PEGylation and 59% palmitoylation with critical micelle concentration (CMC) value of 0.063 mg/mL as suitable to be incorporated with ITZ. The incorporation of PGC-PEG with ITZ (PGC-PEG-ITZ) produced homogenous positively charged formulations of polymeric micelles (PGC-PEG-ITZ-PM) and nanoemulsions (PGC-PEG-ITZ-NE). At drug to polymer ratio of 1:10, PGC-PEG-ITZ-NE showed higher drug entrapment (±80%) compared to that of 1:10 PGC-PEG-ITZ-PM (±40%). The average particle size of 1:10 PGC-PEG-ITZ-PM and PGC-PEG-ITZ-NE was 152-155 nm and 575-590 nm, respectively.